Implementation of Learning Evaluation in the Independent Curriculum: A Case Study at MAN 2 Bogor City - Herlina, Lina; Adawiyah, Riri Robiatul; Khotimah, Aulia Husnul; Arrasyid, Fathan Ahmad (Global Education Journal, 2025)
The Merdeka Curriculum implemented after the Covid-19 pandemic is here as an answer to challenges in the world of education that continues to develop. This curriculum provides space for teachers to innovate, while placing students at the center of learning. The purpose of this study is to observe how the evaluation of learning in the Independent Curriculum is implemented in MAN 2 Bogor City, as well as the various obstacles faced by teachers in the process. This research method uses a qualitative approach with a case study method, involving five teachers as the main informants. The results of the study show that learning evaluation has referred to the principles of the Independent Curriculum, with an emphasis on formative and summative assessments. Teachers prioritize daily assessments that include aspects of student attitude, activeness, and understanding, rather than cognitive assessments alone. However, challenges such as the preparation of comprehensive assessment instruments and lack of active involvement from students are still found. Evaluation is also carried out internally by the school as a form of supervision and quality improvement. Overall, the evaluation of learning at MAN 2 has gone well, but it still needs to strengthen teacher capacity and system support so that the principles of the Independent Curriculum can be applied optimally.